Przymierza outsourcingowe w kształtowaniu przedsiębiorstw sieciowych przez podmioty o tożsamej domenie - Szkic-Czech, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Outsourcing ability to support activities of small companies of identical domain, dominated by high competitiveness in their range is exposed to a complimentary model of network organigram, based and functioning according to outsourcing rules and presented in the article. The main feature of the model is its reference achieved by its ability to solve and to acknowledge brand specificity and structure of business process as being its determining ability to increase the value for customers using the method of decomposing its process of creation and outsourcing creation of chain elements by separate subjects of the complimentary domain. This scientific description is based on research and analysis of specificity of photographic line. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 525-537